Biomimetic race model of the loop between the superior colliculus and the basal ganglia: Subcortical selection of saccade targets. (July 2015) - Thurat, Charles; N'Guyen, Steve; Girard, Benoît
Abstract: The superior colliculus, a laminar structure involved in the retinotopic mapping of the visual field, plays a cardinal role in several cortical and subcortical pathways of the saccadic system. Although the selection of saccade targets has long been thought to be mainly the product of cortical processes, a growing body of evidence hints at the implication of the superior colliculus in selection processes independent from cortical inputs, capable of producing saccades at latencies incompatible with the cortical pathways. This selection ability could be produced firstly by the lateral connections between the neurons of its maps, and secondly by its interactions with the midbrain basal ganglia, already renowned for their role in decision making. We propose a biomimetic population-coded race model of selection based on a dynamic tecto-basal loop that reproduces the observed ability of the superior colliculus to stochastically select between similar stimuli. Our model's selection accuracy depends on the discriminability of the target and the distractors. Our model also offers an explanation for the phenomenon of Remote Distractor Effect based on the lateral connectivity within the basal ganglia circuitry rather than on lateral inhibitions within the collicular maps. Finally, we propose a role for the intermediate layers of the superior colliculus, as stochastic integrators dynamically gated by the selective disinhibition of the basal ganglia channels that is consistent with the recorded activity profiles of these neurons.